Sorting nexin 17 increases low-density lipoprotein receptor-related protein 4 membrane expression: A novel mechanism of acetylcholine receptor aggregation in myasthenia gravis - He, Xiaoxiao; Zhou, Shuxian; Ji, Ying; Zhang, Yingna; Lv, Jie; Quan, Shangkun; Zhang, Jing; Zhao, Xue; Cui, Weike; Li, Wenbo; Liu, Peipei; Zhang, Linyuan; et al. (Frontiers in Immunology, 2022)
Myasthenia gravis (MG) is characterized by autoimmune damage to the postsynaptic membrane of the neuromuscular junction (NMJ) with impaired postsynaptic acetylcholine receptor (AChR) aggregation. Low-density lipoprotein receptor-related protein 4 (LRP4) plays an important role in AChR aggregation at endplate membranes via the Agrin–LRP4–muscle-specific receptor tyrosine kinase (MuSK) cascade. Sorting nexin 17 (SNX17) regulates the degradation and recycling of various internalized membrane proteins. However, whether SNX17 regulates LRP4 remains unclear. Therefore, we examined the regulatory effects of SNX17 on LRP4 and its influence on AChR aggregation in MG. We selected C2C12 myotubes and induced LRP4 internalization via stimulation with anti-LRP4 antibody and confirmed intracellular interaction between SNX17 and LRP4. SNX17 knockdown and overexpression confirmed that SNX17 promoted MuSK phosphorylation and AChR aggregation by increasing cell surface LRP4 expression. By establishing experimental autoimmune MG (EAMG) mouse models, we identified that SNX17 upregulation improved fragmentation of the AChR structure at the NMJ and alleviated leg weakness in EAMG mice. Thus, these results reveal that SNX17 may be a novel target for future MG therapy.